2011
DOI: 10.1073/pnas.1101275108
|View full text |Cite
|
Sign up to set email alerts
|

Methionine sulfoxide reductase A is a stereospecific methionine oxidase

Abstract: Methionine sulfoxide reductase A (MsrA) catalyzes the reduction of methionine sulfoxide to methionine and is specific for the S epimer of methionine sulfoxide. The enzyme participates in defense against oxidative stresses by reducing methionine sulfoxide residues in proteins back to methionine. Because oxidation of methionine residues is reversible, this covalent modification could also function as a mechanism for cellular regulation, provided there exists a stereospecific methionine oxidase. We show that MsrA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 45 publications
2
102
0
2
Order By: Relevance
“…These observations suggest that MsrA possesses other enzymatic activity besides the methionine sulfoxide reductase function that repairs free and bound MetSO. A recent report that MsrA is also a stereospecific methionine oxidase, producing Met-S-SO, raises the possibility that P. aeruginosa MsrA also has additional oxidase-like activity (57). Similar to findings of a previous report (57), the depletion of thioredoxin by paraquat treatment could lead to enhanced methionine oxidase activity and the formation of MetSO in target proteins that render the bacteria more susceptible to paraquat killing.…”
Section: Resultssupporting
confidence: 75%
“…These observations suggest that MsrA possesses other enzymatic activity besides the methionine sulfoxide reductase function that repairs free and bound MetSO. A recent report that MsrA is also a stereospecific methionine oxidase, producing Met-S-SO, raises the possibility that P. aeruginosa MsrA also has additional oxidase-like activity (57). Similar to findings of a previous report (57), the depletion of thioredoxin by paraquat treatment could lead to enhanced methionine oxidase activity and the formation of MetSO in target proteins that render the bacteria more susceptible to paraquat killing.…”
Section: Resultssupporting
confidence: 75%
“…For example, haloalkaliphilic bacterial arsenate reductase can also function as an oxidase (Richey et al 2009). It is not yet clear if MsrA functions as an oxidase by a reversible covalent modification-induced conformational change and/or by interaction with a regulatory protein (Lim et al 2011). Additionally, whether Met oxidase requires an oxidative context to catalyze the forward reaction is unknown.…”
Section: Met Oxidation Is Reversiblementioning
confidence: 99%
“…However, Lim et al (2011) recently reported that MsrA, which reduces the S-epimer of MetSO, can also function as a Met oxidase in catalyzing the forward reaction of Met to S-epimer of MetSO (Fig. 1).…”
Section: Met Oxidation Is Reversiblementioning
confidence: 99%
“…The reaction of oxygen species with methionine leads to the formation of methionine sulfoxide (Met-SO), 4 which comes in two stereospecific types, Met-S-SO and Met-R-SO. Methionine sulfoxides are not only the result of a nonspecific reaction but are also formed after a catalyzed reaction by oxygen-consuming NADPH-dependent enzymes or by the newly identified oxidase activity of MsrA (4 -6), a methionine sulfoxide reductase with stereoselective reductase (7) and oxidase activity (4) toward the S isomer.…”
mentioning
confidence: 99%